DEVELOPING THEME-BASED SUPPLEMENTARY LISTENING MATERIALS FOR THE TENTH GRADERS OF TOURISM SKILLS PROGRAM OF VOCATIONAL HIGH SCHOOL - Ita Permatasari; Muhyiddin Aziz (Humaniora Scientia, 2019)
The main objectives of this research are: (1) to investigate the quality of the existing listening materials in the textbook â€œMandiri-Practice Your English Competence untuk SMK/MAKâ€ used by the tenth graders of tourism skill programs, and (2) to develop theme-based supplementary listening materials for the tenth graders of tourism skills program. In the exploration stage, the researchers investigated the quality of the existing materials by reading/checking the existing textbook, observing the class, interviewing the English teacher, and distributing questionnaire to 25 students. Besides, the researchers conducted need analysis by distributing questionnaire to the students, observing the class, and interviewing the head of the tourism skills program. In the developing stage, the prototype was developed. Three experts in materials development, English for Specific Purposes and Tourism filed were involved to give validation to the prototype before it was tried out to the class. The product has some differences from the existing listening materials. The main differences are: (1) the proposed product consists of listening materials for the tenth graders of tourism skills program while the existing book provided listening materials for general students in senior high school; (2) the product was developed based on theme-based approach while the existing materials was not developed by certain approach; (3) the objectives of the learning were provided in the beginning each unit; (4) there are various listening activities and materials. Hopefully, the final product namely Theme-Based Supplementary Listening Materials for the Tenth Graders of Tourism Skills Program can be useful for both the students and the English teacher in tourism skills program. KeywordÂ  : listening, supplementary materials, theme-based approach, vocational high school, tourism skills program